iCare4U – Mental health support for UiTM Shah Alam students / Amirudin Meroyan - Meroyan, Amirudin (2021)
Online support is one of the essential parts to help people who had related mental health problems. Social support includes providing companions and other people, including family members, to turn to in times of need or emergency to provide you with a larger core and healthy self-image. Some people are afraid to express their feeling and fear of being humiliated if people know about their mental health condition. This project aims to develop mental health support mobile application that focuses on social and peer support to target the user to have a comfortable and easy sharing experience or problems with someone. The scope of this project is for students UiTM Shah Alam who had related mental health problems to seek online support. The most suitable methodology to develop the application is the Mobile Application Development Lifecycle or MADLC. This model will facilitate the production process and allow the application to operate seamlessly and systematically. The significance of these projects is this application would be the best solution for the student that has a low self-confidence or is shy type of person to communicate with an online chat feature. For counselor buddies, it would improve their communication and interpersonal skills, and the counselor will support them to provide a better therapy. In conclusion, iCare4U may support the students that need help to overcome their related mental health problems.